Auditoría de gestión al departamento financiero de la“Escuela Técnica de la Fuerza Aérea”, ubicada en la provincia de Cotopaxi, cantón Latacunga, período del 1 enero al 31 de diciembre del 2014 - Cárate Ronquillo, Katty de las Mercedes (2016)
This research has been developed in the Finance Department at Technical School of “Fuerza Aerea”, the aim has been to establish the fallacies which hinder the efficient development of the operations in this section, since, it had not previously conducted audits Management. This research has used descriptive research the same has been supported by methods as deductive, inductive, analytical, synthetic and statistical which allowed to collect information from areas of budgets, accounting, treasury and fixed assets which together form the Finance Section, where compliance with existing procedures was verified, the evaluation of internal control and finally the application of indicators, It has allowed to have a real picture of the management….